If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1r + -5(2r + 2) = -76 Reorder the terms: -1r + -5(2 + 2r) = -76 -1r + (2 * -5 + 2r * -5) = -76 -1r + (-10 + -10r) = -76 Reorder the terms: -10 + -1r + -10r = -76 Combine like terms: -1r + -10r = -11r -10 + -11r = -76 Solving -10 + -11r = -76 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -11r = -76 + 10 Combine like terms: -10 + 10 = 0 0 + -11r = -76 + 10 -11r = -76 + 10 Combine like terms: -76 + 10 = -66 -11r = -66 Divide each side by '-11'. r = 6 Simplifying r = 6
| 5/7x.25 | | X=3(6y-8) | | 2[2y+2]-5y=1 | | u-2=5 | | 90+x=5x | | n=30-25 | | 8t=3[t+55] | | -7x+3(3x+4)=-10 | | -7x+3(3x+4)=-10 | | (4x^2+12)-(10x^2-11)= | | y=400-.8 | | -7x+3(3x+4)=-10 | | 2+2=q | | 4-2x+2=-64 | | n=40-10 | | 2n^2-6=0 | | 4-2x=10+x | | 10-3b=-7b+6b | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 4y-a=5a+6(3-y) | | Ln40/ln4 | | 2-(1/3)t | | 6+z(9)=9 | | -4(-3x-8)-4x+8= | | 15/30=6/x | | -100=n+8 | | -100=n+8 |